Effect of Using Fermented Moringa Leaf Flour (Moringa oleifera) in Diets on Broiler Fat Deposition - Fenita, Yosi; Warnoto, Warnoto; Santoso, Urip; Nurmeiliasari, Nurmeiliasari; Hindrianti, Hindrianti; Rafian, Teguh (Jurnal Sain Peternakan Indonesia, 2023)
This study aims to evaluate the effect of using fermented Moringa oleifera leaf flour in the diet on broiler fat deposition (percentage of neck fat, heart fat, proventriculus fat, gizzard fat, abdominal fat, and sartorial fat). The research was conducted from 20 August to 25 September 2021 at the Commercial Zone and Animal Laboratory (CZAL) of the Animal Husbandry Department and the Animal Husbandry Laboratory, Faculty of Agriculture, Bengkulu University. The design used was a Completely Randomized Design (CRD) with four treatments, five replications, and each replication consisting of 8 chickens. The variables observed were the percentage of abdominal fat, sartorial fat, gizzard fat, heart fat, proventriculus fat, and neck fat. The results showed that the treatment had no significant effect (P>0.05) on gizzard fat, heart fat, and neck fat but had a significant effect (P<0.05) on abdominal fat, sartorial fat, and proventriculus fat. The percentage of gizzard fat ranges from 0.263% - 0.320%, heart fat ranges from 0.026% - 0.036%, neck fat ranges from 0.020% - 0.031%, abdominal fat ranges from 0.334% - 0.441%, sartorial fat ranges from 0.163% - 0.217%, and proventriculus fat ranges from 0.024%. % - 0.038%. It was concluded that using fermented Moringa oleifera leaf flour up to a level of 15% could not reduce gizzard fat, heart fat, and neck fat in broilers. Still, it improved abdominal fat, sartorial fat, and proventriculus fat.